IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 114 TAHUN 2014 DALAM PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (RPJMDES) DESA LUBUK RAJA KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN TAHUN 2015 - Al Barru, Dhobit; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the problems of the implementation of theMinister of Home Affairs Regulation No. 114 of 2014 on the Village DevelopmentGuidelines in the preparation of RPJMDes in Lubuk Raja Village. This study aimsto determine the Stages of RPJMDes 2016-2021 Preparation in Lubuk Raja Villageand to determine the inhibiting factors in the stage of Preparation of RPJMDes2016-2021 in Lubuk Raja Village Bandar Petalangan District Pelalawan Regencybased on the Minister of Home Affairs Regulation No. 114 of 2014 About theguidelines of Development Village. This study using Gow and Morss theoryreveals that obstacles in policy implementation. Primary information sources(informants) is determined by purposive sampling and the necessary data iscollected by interviewing techniques and literature study.The results of this study indicate that the formation of RPJMDes DraftingTeam in Lubuk Raja Village did not include women in the preparation ofRPJMDes, Aligning the policy direction of district development planning,conducted by socializing the Rural Area Development Plan. Village situationassessment only focuses on Dusun one Lubuk Raja Village, Development of villagedevelopment plan through village meetings where the participants who attend theVillage Deliberation are very few and lack of understanding of RPJMDesCompilation Team. Inhibiting factors in the stages of RPJMDes Development inLubuk Raja Village consists of internal constraints, namely Institutional weaknessand weak resource, human resource in the field of Technical and Administration.In addition, external factors are Political, Economic and Environmental Barriers,Shortages in Technical Assistance, Lack of Decentralization and Participation, LessSupporting Information Systems, and Technological Factors.Keywords: Implementation Village Policy, RPJMDes Stages